Art and Aesthetics of Ginga: Boundary for the Future in the in-Between Places of Diversity (Global Journal of Human-Social Science, 2013)
This article aims to reflect critically the possibility of educational practices guided by multiculturalist perspective, seeking to consolidate a Border Pedagogy based on what we stand for as an aesthetic of ginga. Discussing the aesthetics originating from emerging and miscegenation scenarios that the interculturality becomes possible to propose such as the art as the space in which through between boundaries enable us for the exercise of rediscovering other margins in the center of another story. None of this would be possible in our reading, whether the way for dialogue and experimentation to our actions were not the arts. This means that the arts are the ground which enables us deterritorialization of socially constructed norms and dogmas. In our activities, the arts were essential for stimulating reflection on the importance of valuing the diversity as a factor in social development.
Keywords: border pedagogy; aesthetics of ginga; diversity and multiculturalism